The micro-dimensions of health policy design: evidence from a comparative analysis - Azad Singh Bali (19247911) (2024)
Policy design studies typically focus on broad policy goals and the types of tools that governments use to realize them. There is however limited scholarly understanding of how these goals and tools are operationalized “on-the-ground.” In this paper, we apply Capano and Howlett’s 2024 Framework on the Micro-Dimensions of Policy Design to understand how universal health coverage goals in the United States, Singapore, and Thailand are operationalized. The framework unpacks the “nuts and bolts” of policy design particularly the specification of policy targets and tools. A comparative analysis of three programs (Obamacare in the US, Medisave in Singapore, and Universal Coverage Scheme in Thailand) demonstrates how similar high-level policy goals are pursued through different tools and settings. Studying these micro dimensions provides insights into the actual operational ways in which high-level objectives are translated into impacts at the ground level. From an applied point of view, a comparative focus on the dimensions of the micro level of policy design is useful for generating evidence and informing health policy debates about what works or does not work on-the-ground. Other Information Published in: Policy Design and Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/25741292.2024.2356332